Skeletal-dental features in 33 bull terrier dogs - Monica C. Martins; Sara A. Valadares; Jerzy P. Gawor; Lisa A. Mestrinho (BMC Veterinary Research, 2022)
Abstract Background The Bull terrier breed has been reported in the veterinary literature to suffer frequent dental and skeletal malocclusions. In this retrospective case series, we report skeletal-dental anomalies in a group of 33 Bull terriers presented for a dental consultation. Results Out of 33 dogs examined, 24 cases had full mouth radiography or Cone-beam computed tomography performed. Eruption and development abnormalities observed were as follows: hypodontia in 54.1% (13/24), eruption changes in 29.2% (7/24), and tooth shape abnormalities in 33.3% (8/24). All dogs presented with some type of dental or skeletal malocclusion: neutroclusion was the most common (66.7% of the animals), followed by mandibular mesioclusion (18.8%), maxillo-mandibular asymmetry (9.4%), and mandibular distoclusion (6.3%). Dental abnormalities noted included rotation of mandibular and maxillary premolar teeth, distal displacement of the incisor teeth, lingual displacement of the mandibular canine teeth, and absence of mandibular premolar and molar teeth. Lingual displacement of mandibular canine teeth was associated with malocclusion causing trauma (odds ratio 7.1, 95% confidence interval [1.4 to 36.1], p = 0.024). Conclusions Malocclusions and tooth shape abnormalities were found to be the most frequent finding in this group of Bull terriers. Although these findings cannot be generalized to the global population further studies are needed to observe the true expression of these anomalies in the general breed population.